2004
DOI: 10.1063/1.1686906
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of cobalt and cobalt–platinum nanocrystals investigated by magneto-optical Kerr effect

Abstract: Magneto-optical Kerr effect, is used to investigate the magnetization of film made of uncoalesced cobalt and cobalt-platinum nanocrystals. For the pure cobalt nanocrystals, different film morphologies are obtained through application of magnetic field during deposition. These morphologies have quite different magnetic properties, which is rationalized by considering dipolar interactions and the associated demagnetizing factor. We show that fast annealing can be used to trigger changes in the particles' crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…Interestingly, the mean anisotropy constant is consistent with the value of K eff previously reported for similar unselected CoPt clusters [13]. Note also that the same order of magnitude for the anisotropy constant has been reported in the case of chemically synthesized CoPt A1 nanoparticles [19]. Following the theoretical considerations of Tournus et al [20], we can attribute the K eff dispersion mainly to the multiplicity of atomic configurations: a huge number of chemical arrangements can indeed statistically exist in the case of chemically disordered particles of the same geometry size and shape, corresponding to different values of E ani and hence K eff .…”
Section: Magnetometry Measurementssupporting
confidence: 84%
“…Interestingly, the mean anisotropy constant is consistent with the value of K eff previously reported for similar unselected CoPt clusters [13]. Note also that the same order of magnitude for the anisotropy constant has been reported in the case of chemically synthesized CoPt A1 nanoparticles [19]. Following the theoretical considerations of Tournus et al [20], we can attribute the K eff dispersion mainly to the multiplicity of atomic configurations: a huge number of chemical arrangements can indeed statistically exist in the case of chemically disordered particles of the same geometry size and shape, corresponding to different values of E ani and hence K eff .…”
Section: Magnetometry Measurementssupporting
confidence: 84%
“…We conclude that for any nanoparticle assembly method, precise control of the interface structure, at least in the first atomic layers, will be a crucial issue if reproduceable exchange interactions are desired. In particu- lar, cobalt nanoparticles prepared using wet chemistry methods [54][55][56][57] are not likely to have consistent interface structures, and are therefore likely to have highly variable interactions. Here we note that some authors have concluded theoretically 7,43 that the atop-fcc interface between graphene and Co(0001) is energetically slightly preferred to atop-hcp.…”
Section: Discussionmentioning
confidence: 99%
“…A system which has been intensively investigated experimentally [3,4,5,6,7,8,9,10] as well as theoretically [11,12,13,14,15] in recent years is Co/Pt(111) (used here as a short notation for Co clusters or nanostructures, respectively, deposited on a Pt(111) substrate) as this is a prototype to study the requirements on new high-density magnetic storage materials. Earlier theoretical works studied only rather small Co clusters or Co chains on Pt(111) [11,12,13,14], whereas only recently first qualitative results and trends based on a parameterised tight-binding approach were published for deposited structures of up to 37 Co atoms [15].…”
Section: Introductionmentioning
confidence: 99%